DEVELOPMENT OF TEACHERS' TIME MANAGEMENT SKILLS TO IMPROVE MADRASAH LEARNING PRODUCTIVITY - Sultoni, Muhammad Fahim (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to investigate and develop teachers' time management skills as an effort to increase learning productivity in the educational environment. Dynamic changes in teachers' job demands, along with the complexity of their duties, drive the need to understand and master effective time management skills. This research involved the development of a specific training program designed to increase teachers' understanding and implementation of efficient time management practices. The research method used involved an initial survey to assess teachers' level of awareness and needs regarding time management, followed by the design and implementation of an appropriate training program. Data obtained through surveys, observations and interviews were used to evaluate the impact of the training program on teachers' time management skills and, as a result, on classroom learning productivity. The research results showed a significant increase in teachers' understanding and application of time management skills after attending the training program. Teachers involved in the training reported positive changes in time management efficiency, reduced stress, and increased focus on the learning process. The practical implications of this research highlight the importance of developing teachers' time management skills as an effective strategy for increasing learning productivity in educational settings